Halloysites as carriers for Ce(III) ions in anti-corrosive paint for steel - Roselli, Sol Natacha (2023)
Aluminosilicates minerals are used as inhibitive cation carriers to protect metals from corrosion. The objective of this paper was to study the anticorrosive behaviour of natural halloysite, loaded with ions Ce(III) or La(III), as carrier pigment to inhibit steel corrosion. The mineral was characterized by Fourier transform infra-red spec troscopy and x-ray diffraction. Steel in contact with the loaded mineral and immersed in NaCl 0.05 M solution was study by electrochemical tests, scanning electron microscopy and energy dispersive x-ray analysis. Besides alkyd solvent paints were formulated, prepared, and tested (salt spray and humidity chambers exposure and electrochemical tests) employing the loaded halloysite together with or without zinc phosphate. Results showed that the protective action of the paints applied on SAE 1010 steel depends on the loaded cation and on the environment to which they were exposed.